Repair of a medial canthal defect - Alberto Murtas; Virginia Maffei; Fabrizio Fantini (PAGEPress Publications, 2024)
An 87-year-old man presented for treatment of a histology-proven basal cell carcinoma involving the left medial canthus. The lesion was successfully resected with adequate margins under local anaesthesia and resulted in a defect measuring 2 x 1.5 cm. How would you repair this defect?